DNA Damage in Healthy Individuals and Respiratory Patients after Treating Whole Blood In vitro with the Bulk and Nano Forms of NSAIDs - Najafzadeh, Mojgan; Normington, Charmaine; Jacob, Badie K.; Isreb, Mohammad; Gopalan, Rajendran C.; Anderson, Diana (Frontiers in Molecular Biosciences, 2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) inhibit COX enzyme activity which affects the inflammatory response. Inflammation is associated with increasing cancer incidence. Pre-clinical and clinical studies have shown that NSAID treatment could cause an anti-tumour effect in cancers. In the present study, blood was taken from healthy individuals (n=17) and patients with respiratory diseases or lung cancer (n=36). White blood cells (WBC) were treated with either a micro-suspension, i.e. bulk (B) or nano-suspension (N) of aspirin (ASP) or ibuprofen (IBU) up to 500 µg/ml in the comet assay and up to 125 µg/ml in the micronucleus assay. In this study results were compared against untreated lymphocytes and their corresponding treated groups. The results showed, thgat NSAIDs in their nano form significantly reduced the DNA damage in WBCs from lung cancer patients in bulk and nano compared to untreated lymphocytes. Also, there was a decrease in the level of DNA damage in the comet assay after treating WBCs from healthy individuals, asthma and COPD groups with aspirin N (ASP N) but not with IBU N. In addition, the number of micronuclei decreased after treatment with NSAIDs in their nano form (ASP N and IBU N) in the healthy as well as in the lung cancer group. However, this was not the case for micronucleus frequency in asthma and COPD patients. These data show that lymphocytes from different groups respond differently to treatment with ASP and IBU as measured by comet assay and micronucleus assay, and that the size of the suspended particles of the drugs affects responses.